Assess a method for the parametrization of urban quality of life - Eusuf, Muhammad Abu; Salleh, Md Noor; Mamun, Abdullah Al; Ibrahim, Mansor (2017)
From the myriads of research and case study, it is observed that the assessment of the urban quality of life (QoL) has been based on the various parameters and factors. Besides, the design and construction industries have an increasing attention in and concern for environmental effects over its total life cycle of urban fabrics. Although a significant form of literature has provided positive indication as auxiliary to the effects of natural environments on urban comfort. Little has been known about the specific spatial patterns of urban nature as parametric-relation to the urban QoL. Urbanization processes in Malaysia have become an integral part of the various parametric matrix confronted by rapid growth. The essential parameters and factors need to be parametrized in order to design a futuristic urban location on the stressed situation, a recent overwhelming growth of urbanization. This research investigated a method in order to accumulate the parameters and factors those are guided the urban Quality of Life under a stressed condition. The main objective of the research is to parametrize the urban environment at the multidimensional scale and that needed to be investigated. There are many approaches to assessing this interdisciplinary term QoL where may focus this issue using experimental and observational process. For the analysis of collected data here employed a parametric valid model with a significant integration of various parameters and factors related to quality of living conditions. The analytical results displayed the vital importance of the most effective environmental mitigation strategies in micro level. This scenario is also contributed to the significant mitigation of microclimate on the improvement of Urban QoL. The benefits of the parametric study are exaggerated, when applied on a spatial scale larger than the urban neighborhood scale. We use this scale to measure the quality of life in the city of Malaysia.